Randomized Controlled Trial on the Influence of Intraoperative Remifentanil versus Fentanyl on Acute and Chronic Pain after Cardiac Surgery. Issue 4 (28th September 2017) - de Hoogd, Sjoerd; Ahlers, Sabine J.G.M.; van Dongen, Eric P.A.; van de Garde, Ewoudt M.W.; Daeter, Edgar J.; Dahan, Albert; Tibboel, Dick; Knibbe, Catherijne A.J.
Abstract: Background: Remifentanil has been associated with increased acute and potentially chronic postoperative pain. The objective of this prospective randomized controlled trial was to investigate the influence of intraoperative remifentanil on acute and chronic postoperative pain after cardiac surgery. Methods: Patients ( N = 126) receiving standardized anesthesia with propofol and intermittent intravenous fentanyl at predetermined times for cardiac surgery were randomized to intraoperatively receive either a continuous remifentanil infusion or additional intermittent intraoperative fentanyl as needed. The primary endpoint was chronic thoracic pain at 12 months after surgery. Secondary endpoints were pain at 3 and 6 months after surgery and analgesic requirements and pain levels in the first 72 hours. Results: There was no significant difference in incidence of chronic thoracic pain between the remifentanil and fentanyl groups, respectively (20% vs. 18%; P = 0.817). At 3 months, however, significantly more patients in the remifentanil group reported chronic thoracic pain (51% vs. 33%; P = 0.047). This effect was more pronounced in younger patients and in patients receiving a higher dose of remifentanil (both P < 0.05). The first 24 and 48 hours postoperatively, morphine consumption in the remifentanil group was significantly higher than in the fentanyl group (34.3 mg [interquartile range (IQR) 25.3 to 48.2] vs. 30.2 mg [IQR 19.2 to 38.1], P = 0.028; and 46.8 mg [IQR 33.8 to 59.2] vs. 39.0 mg [IQR 6.2 to 51.4], P = 0.047, respectively). Conclusions: Intraoperative use of remifentanil during cardiac surgery does not impact chronic postoperative pain 1 year after surgery. Nevertheless, remifentanil increases analgesic requirements and thoracic pain until 3 months after surgery, and its use is therefore less favorable during cardiac surgery.